Endocytic sorting motif interactions involved in Nef-mediated downmodulation of CD4 and CD3 - Santiago Manrique (Nature Portfolio, 2017)
HIV and simian immunodeficiency virus (SIV) Nef proteins both stimulate the clathrin-mediated endocytosis of CD4 but differ in downmodulation of the immune receptor CD3. Here, the authors present the structure of SIV Nef bound to the ExxxLM motif of another Nef molecule, which allows them to propose a model how Nef recognizes these motifs in CD3 and CD4.